Implications of Pesticide-Related Deaths on Forensic Entomological Investigations and the Elucidation of Secondary Pesticide Bioaccumulation in Blowfly Tissues - Marlini, Othman (Universiti Malaysia Sarawak, 2025)
In forensic entomology, insect’s development and succession pattern associated with decomposing carrion can become a useful information in the estimation of post-mortem interval. Several external factors such as environment, corpse’s condition and the presence of toxins or chemicals can alter the rate of development, insects’ arrival, and the duration of decomposition of the carrion. The objectives of this study were to investigate the effects of pesticides on the development rate of blowflies, carrion decomposition and insect succession pattern. Besides, this study also aimed to detect the presence of pesticides in larval tissue of the colonising insects. Three types of pesticides were used in this study; glyphosate (herbicide), chlorpyrifos (insecticide) and coumarin (rodenticide). Several concentrations of these pesticides were spiked into the meat substrate and then the blowfly eggs were placed on the substrate. The development duration and stages of the blowfly from eggs to adulthood were observed and recorded. The finding showed that the larvae did not survive at the higher concentration of glyphosate and chlorpyrifos-treated meat substrate. Meanwhile, the larvae in coumarin survived until puparial stage, but the adult failed to emerge. For subsequent experiment, the pesticides were orally administered to rats (Rattus norvegicus), and then euthanised and brought to the study site, at a secondary forest in Kuching, Sarawak. The decomposition stages and duration were observed and compared with control carcasses. The insect succession pattern was also recorded and collected for species identification. The third instar larvae were also collected for toxicological analysis. From the field experiment, a total of 1,579 insects were collected in three trials of experiments. The insects are belonging to nine families from five orders with Chrysomya rufifacies (71.5%) was the predominant species infesting on the carcasses, followed by Chrysomya megacephala and Hemipyrellia ligurriens. The decomposition of the carcasses was consisted of five stages which include; fresh, bloated, active decay, advanced decay and dry remains stage. The carcasses decomposition duration was delayed for carcasses in chlorpyrifos group (17-21 days), followed by coumarin (~11-12 days) and glyphosate (~8 days) compared to control group (~7 days). During the early stages of decomposition process, the species that were first to arrive was blowflies (Calliphoridae), followed by flesh flies (Sarcophagidae) and muscid flies (Muscidae). The sequence of insect succession in control and pesticide-treated carcasses were similar. During the active decay stage, the larvae were actively infesting the carcasses’ tissues except for chlorpyrifos carcasses as the oviposition did not occur, hence the carcasses did not decay by larvae activities. Only few adult flies observed visiting the chlorpyrifos group. Besides adult flies, the wasps were also seen at the site to predate on the flies. During the late stage of decomposition process, few beetles (order: Coleoptera) were seen at the site along with other insects such as Dermaptera. The third instar larvae on the carcasses were collected and brought to the laboratory for toxicological analysis. The specimens were analysed and successfully detected the trace amount both of the analyte, glyphosate and coumarin using Ultraviolet visible spectrophotometer and Gas chromatography mass spectrometry. In conclusion, the findings obtained from this study has indicated that the pesticides altered the fly larvae development and interfered with the decomposition duration of carrion as seen in the field experiment. The changes of larvae development rate were probably caused by the accumulation of the pesticides inside the larvae tissues in which can be detected and quantified. Therefore, the entomological data in this study is important in estimation of post-mortem interval where the presence of pesiticides was suspected.